2020
DOI: 10.1017/s0033291720002767
|View full text |Cite
|
Sign up to set email alerts
|

‘Too many BeEPs in our teens!’ Behavioral and emotional problems in a large group of Italian adolescents

Abstract: Background One in six adolescents suffers from mental health problems. Despite the presence of general information on Italian adolescents' mental health, researches conducted with standardized assessment tools are scarce in the literature. We evaluated the prevalence of self-reported behavioral and emotional problems in a group of Italian adolescents and examined their relation to socio-demographical variables. Methods This population-based sampling survey was conducted on high school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(95 reference statements)
1
1
0
Order By: Relevance
“…Because thought problems were the second most important bridge to SH, preventive interventions should be oriented to adolescents who may experience temporary difficulties in distinguishing reality from fantasy and exhibit disorganized thoughts. Thought problems are not uncommon in community adolescents, with a prevalence of up to 7-8% among those aged 13 to 18 years [62], and-in our studythought problems were uniquely associated with SH and other risk-taking behaviors. Given the relatively high prevalence, our findings emphasize the importance of addressing maladaptive beliefs related to emotion regulation, particularly among adolescents who are more prone to experiencing psychotic-like experiences.…”
Section: Discussionsupporting
confidence: 51%
“…Because thought problems were the second most important bridge to SH, preventive interventions should be oriented to adolescents who may experience temporary difficulties in distinguishing reality from fantasy and exhibit disorganized thoughts. Thought problems are not uncommon in community adolescents, with a prevalence of up to 7-8% among those aged 13 to 18 years [62], and-in our studythought problems were uniquely associated with SH and other risk-taking behaviors. Given the relatively high prevalence, our findings emphasize the importance of addressing maladaptive beliefs related to emotion regulation, particularly among adolescents who are more prone to experiencing psychotic-like experiences.…”
Section: Discussionsupporting
confidence: 51%
“…Although thought problems refer to strange perceptions, odd beliefs, and unusual behaviors, often associated with the positive symptoms of schizophrenia, psychotic-like experiences appear in several mental disorders [ 54 ] and are not uncommon in adolescents (e.g., up to 7.5% of adolescents between 13 and 18 years of age) [ 55 ]. Similarly, a recent Italian study estimated the prevalence of YSR Thought Problems to be approximately 6% in a large community sample [ 56 ], while another study showed the high diffusion of psychotic-like experiences in the Italian high-school population [ 57 ]. Considering the epidemiological data, our results suggest that adolescents with typical development may have transient difficulties with reality testing and disorganized thoughts, make errors in judgment, overlook probabilities and outcome information, and ultimately exhibit a high propensity for risk.…”
Section: Discussionmentioning
confidence: 99%